Kinetics of the thermal degradation of phenolic compounds from achiote leaves (Bixa orellana L.) and its effect on the antioxidant activity (2022)
ABSTRACT: This work evaluates the effect of temperature and soluble solids on the degradation rate of phenolic compounds, and antioxidant activity of extracts from Bixa orellana L. leaves. The temperatures were studied in the range of typical food processes (70-90 °C) and food storage (−20-37 °C). The results showed that the thermal degradation of the phenolic compounds follows first-order kinetics, in which the degradation rate depends on the temperature, the amount of soluble solids, and the pH. The loss of antioxidant activity also follows first-order kinetics. Under different storage conditions, the half-life times of the total phenols were in the range 40.72-202.47 days, while for the antioxidant activity, the half-times were from 55.87-68.83 days for the ABTS and from 57.85-107.03 days for the FRAP method. The antioxidant activity of the extracts follows the same pattern of thermal degradation as the phenolic compounds. Therefore, we conclude that antioxidant activity is due to its phenolic compounds.